Live Coding the Global Hyperorgan: The Paragraph environment in the indeterminate place. - Petersson, Mattias (Organised Sound, 2023)
This article presents several scenarios in which a live coding environment called Paragraph was utilised to telematically play networked and geographically distributed hyperorgans. Situated within the framework of the Global Hyperorgan project, the TCP/Indeterminate Place Quartet have explored the affordances of the organ network through the concept of Tele-Copresence. By outsourcing certain dimensions of the parameter space of the Paragraph language to other members of the quartet, a shared instrumentality is enabled, where the organs are collaboratively controlled by means of this system. Rooted in a personal composer-performer practice and studied from the perspective of the live coder, the Paragraph system, adapted to the TCP/Indeterminate Place environment, can be understood as a modular system of human and non-human agents, into which the other musicians are patched. The distributed parameter space utilised, thus resembles a shared cantus firmus , a foundational, but dynamically changing, ecology for the live coder to play within.